ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, TRANSFER PEMERINTAH PUSAT DAN EFESIENSI BELANJA DAERAH TERHADAP KEMANDIRIAN KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI SUMATERA UTARA - Anggi Pratama Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
This study aims to analyze the influence of local revenue variables, central government transfers, and efficiency of local expenditure, to the regional financial independence. This study collects empirical evidence. The population in this study were all districts / cities in North Sumatra Province period 2011- 2013, and the sample in this study amounted to 28 districts / cities in the Province of North Sumatra. In this thesis research writer use causal associative research design. Sampling method in this research is by purposive sampling method. The type of data used by the author is secondary data and data processing is done by using statistical program tool. Classical assumption test used by writer include normality test, multicollinearity test, and heterokedastisitas test. While the research model used by the authors is to use statistical analysis of multiple linear regression equation, as for hypothesis testing is done by simultaneous significance test, partial significance test, and coefficient determinant. Based on the result of research, it is known that the variable of original revenues, central government transfers, and efficiency of regional expenditure, simultaneously significant influence to the regional financial independence. Partially, local revenue variable, central government transfers have a significant effect on local financial independence. However, the efficiency of local expenditure has no positive effect on local financial independence.